Intelligent controller based WECS fed unified power flow conditioner for PQ enhancement - Kumar, Polishetty Vinay; Ganapathi, Balamurugan; Kartigeyan, Jayaraman (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
The dominance of non-linear loads, sustainable energy sources and power electronic devices in modern power system has in turn compromised the system stability by introducing numerous power quality (PQ) issues.  A wind energy conversion system (WECS) fed unified power flow conditioner (UPFC) architecture is suggested in this work since maintaining optimal PQ is important for both the supply authorities and customers. The proposed approach supports both clean energy generation and PQ enhancement. The UPFC aids with accomplishing control over reactive power flow, active power flow, phase angle, impedance and voltage. The reference current for the UPFC is generated using DQ theory. Moreover, a shunt and series compensators of an UPFC are controlled using cascaded fuzzy logic controller (CFLC). The stability of the DC voltage obtained from doubly fed induction generator (DFIG) based WECS is also controlled using a CFLC. The simulation model for the presented WECS fed UPFC is developed in MATLAB and its performance is evaluated.